(3QSGdI aj GdHjGV GdPi jXgQ aj GdHOfs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3bGd Cf gPg GdYdI JMOK Yf GdNdW GdHdZei GdPi jUh Edi YVh ef GdCYVGA hjVYa GdbhI GdgGVeI s
(3BNQgG (B:s
(3hcGf ai HYV GdCYVGA GdMSGSI GdJi jecf ajgG GdbWY JeJ QSGdI KGHJ Hf bQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs